Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1365-246x.2006.02864.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave tomography: finite-frequency effects lost in the null space

Abstract: S U M M A R YWe compared surface wave tomography models obtained using finite-frequency kernels and ray theory. We systematically changed regularization in both cases and plotted data misfit against the number of independent parameters in the solution. Our tests show that models from finite-frequency kernels and ray-theoretical kernels are statistically similar. This means that any model obtained using one forward theory can be obtained using the other one by appropriately changing the damping constant. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 39 publications
4
66
1
Order By: Relevance
“…A few studies stressed that tomographic results using the finite-frequency theory are superior to those using the traditional ray theory (a great-circle path assumption under high-frequency approximation) (e.g., Zhou et al 2005). However, other studies (Sieminski et al 2004;Levshin et al 2005;Trampert and Spetzler 2006) found that results using the ray theory are similar to those of the finite-frequency theory when utilizing reasonable ray coverage in the study region. Sieminski et al (2004) further pointed out that finite-frequency effects can be counterbalanced by a physically-based regularization of the tomographic inversion or dense ray coverage in the study region (e.g., Levshin et al 2005).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…A few studies stressed that tomographic results using the finite-frequency theory are superior to those using the traditional ray theory (a great-circle path assumption under high-frequency approximation) (e.g., Zhou et al 2005). However, other studies (Sieminski et al 2004;Levshin et al 2005;Trampert and Spetzler 2006) found that results using the ray theory are similar to those of the finite-frequency theory when utilizing reasonable ray coverage in the study region. Sieminski et al (2004) further pointed out that finite-frequency effects can be counterbalanced by a physically-based regularization of the tomographic inversion or dense ray coverage in the study region (e.g., Levshin et al 2005).…”
Section: Introductionmentioning
confidence: 81%
“…Sieminski et al 2004;Levshin et al 2005;Trampert and Spetzler 2006). Also, the relationship between lateral velocity variation and azimuthal variation is weak (cf.…”
Section: Tomographic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While in seismology, these benefits are still overshadowed by incomplete data coverage ͑Van der Hilst and De Hoop, 2005;Trampert and Spetzler, 2006͒, the seismic applications clearly suffer less from lack of data. This is illustrated by two examples of finite-frequency wave theory in seismic imaging experiments.…”
Section: Seismic Applicationsmentioning
confidence: 99%
“…In parallel, several studies questioned whether the benefits from using BDT, rather than simple RT, could be smaller than the uncertainty posed by the subjective regularisation of the inverse problem (e.g. Sieminski et al, 2004;Trampert and Spetzler, 2006;Van der Hilst and de Hoop, 2005;Boschi et al, 2006). It seems pertinent that tomographers ask what are the consequences on seismic models of the subjectivity inherent to the choice of regularisation parameter.…”
Section: Introductionmentioning
confidence: 99%